PLEK2: a potential biomarker for metastasis and prognostic evaluation in uveal melanoma - Liu, Yichong; Wang, Haiyue; Zhang, Qian; Gao, Xiaodi; Ji, Yiqing; Zhu, Yuanzhang; Zhang, Jingjing; Luo, Wenjuan (Frontiers in Medicine, 2024)
Background: Uveal melanoma (UVM) is an aggressive tumor known for its high metastatic rate, making it necessary to delineate potential molecules that may promote the development of UVM. PLEK2 has been found to promote the progression and metastasis of some tumors, but its role in UVM has not yet been reported. Through this study, we hope to explore the effect of PLEK2 on the prognosis of UVM patients and to discover the potential functional role and intrinsic mechanism of PLEK2. Methods: The GEO datasets GSE211763 and GSE149920 were analyzed using GEO2R to identify differentially expressed genes that may be associated with UVM progression and metastasis. A Protein-Protein Interaction Network (PPI) was constructed to identify key molecules. The correlation between PLEK2 expression and overall survival was evaluated via GEPIA2, and clinical characteristics of UVM patients were compared based on PLEK2 levels. PLEK2 expression in UVM cell lines was assessed using the CCLE database and confirmed by qPCR and western blot. A weighted correlation network analysis (WGCNA) was performed, followed by gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Finally, a search for miRNAs potentially regulating PLEK2 expression was performed using TargetScan, miRWalk, and TarBase databases. Results: Comparative analysis of the GEO datasets unveiled 79 commonly up-regulated genes and 238 commonly down-regulated genes. The PPI network identified 9 hub genes, with PLEK2 significantly linked to reduced overall survival. Clinical comparisons indicated significant differences in cancer status (p = 0.013) and tumor diameter (p = 0.039) between high and low PLEK2 expression groups. Elevated PLEK2 mRNA levels were confirmed in UVM cell lines compared to retinal pigment epithelial cells. PLEK2 was enriched in the calcium signaling pathway and associated with the WNT/Ca2+ signaling pathway. A total of 21 miRNAs potentially regulating PLEK2 were predicted. Conclusion: PLEK2 is upregulated in UVM and correlates with poor patient prognosis, likely influencing the calcium signaling pathway. PLEK2 represents a promising prognostic biomarker and therapeutic target for UVM.